Beschäftigung Älterer in Deutschland: der unvollständige Paradigmenwechsel - Werner Eichhorst (Institute for the Study of Labor (IZA), 2006)
Despite a sequence of labor market reforms in recent years, employment of older workers in Germany is still lower than in many other European countries. The paper explains this by institutional factors that affect labor supply, labor demand and matching, i.e. labor market regulation, human capital formation, wages as well as the availability of active labor market policy and social benefits. It can be shown that the institutional framework currently in place in Germany is inconsistent. Further reforms are needed to create better employment opportunities for older workers. This implies the abolishment of still existing incentives for early retirement, a more flexible labor law, stronger capacities for human capital formation through life-long learning and a consistent strategy to activate older job seekers.
Keywords: J26; J48; J68; 330; older workers; early retirement; labor market policies; Germany; Ältere Arbeitskräfte; Erwerbstätigkeit; Arbeitsmarktpolitik; Deutschland